1878-79 Ga. Laws 142 - (:unkn) unknown (My University, 1879)
An Act for the Protection of Birds and Game in the County of Bibb, § 1: Prohibited hunting between April 1 and October 1 in the County of Bibb
Keywords: HUNTING REGULATION